EPID-13. ISOLATED PITUITARY STALK THICKENING (IPST) IN CHILDREN: NATURAL HISTORY AND PREDICTORS OF NEOPLASTIC DISEASE. Issue 2 (22nd June 2018) - Skrypek, Maggie; Brown, Anastasia; Pape-Blabolil, Julie; Bendelsmith, Charles; Patel, Sachin; Patterson, Richard; Jennifer Abuzzahab, M; Ingram, Katherine; Linabery, Amy; Bendel, Anne
Abstract: Isolated pituitary stalk thickening (IPST) is rare, frequently discovered while evaluating diabetes insipidus (DI), and has a broad differential diagnosis including malignancy. A retrospective chart review was performed to characterize the outcome of IPST. We reviewed the medical records of 365 patients <21 years of age with a diagnosis of DI seen at Children's Minnesota between 11/2003 and 1/2018. Patients were eligible if brain MRI showed IPST, with "pituitary stalk thickening" defined as a pituitary stalk diameter >3 mm and "isolated" defined as a negative initial workup for pituitary thickening. Ten children were identified with IPST, with a male:female ratio of 6:4 and median age at diagnosis of 8.3 years (range: 3 days-19 years). Median follow-up was 5.1 years (range 0.5-9.6 years). At diagnosis, maximum pituitary stalk diameters (MPSD) ranged from 3.1-6.0 mm. During follow-up, 5 patients had resolution of IPST between 0.5-4.2 years from diagnosis (MPSD ranged from 3.3-12.0 mm), 3 remained minimally changed between 1.0-7.7 years from diagnosis (MPSD: 0.5-8.0 mm), and 2 showed asymptomatic progression of IPST between 6-8 months from diagnosis (MPSD: 7.0-17.0 mm). The 2 patients with progressive IPST underwent biopsy of the pituitary stalk and were diagnosed with a germinoma and craniopharyngioma. In conclusion, IPST typically remains stable or improves over time, but 20% of IPST may harbor a malignancy. Follow-up brain MRI is indicated, and progressive growth warrants further workup and potential biopsy to rule out malignancy. A detailed workup and follow-up algorithm for IPST will be discussed in the presentation.